Improvement of Clinical Practice Guideline Appraisal by Human Experts and AI Agents by Using Structured Guidance: Systematic Review, Meta-Analysis, and Validation Study - Xingrun Mao; Junhao Wang; Zezhang Wang; Yuwei Zhang; Shiyu Qiu; Jingyu Ye; Shiyan He; Chongyang Wang; Yong Xia; Chengqi He; Ke Li; Siyi Zhu (Journal of Medical Internet Research, 2026)
Background Rehabilitation clinical practice guidelines (CPGs) have increased rapidly, but inconsistent methodological quality limits their implementation. Although Appraisal of Guidelines for Research and Evaluation II (AGREE II) and Reporting Items for Practice Guidelines in Health Care (RIGHT) provide standardized appraisal frameworks, their application is time-consuming. Large language model (LLM)–based AI agents may offer a scalable alternative with uncertain reliability. Objective We evaluated rehabilitation CPGs’ methodological and reporting quality and determined whether structured guidance improves human expert–AI agent agreement. Methods We systematically reviewed English- and Chinese-language rehabilitation CPGs from Embase, Scopus, PubMed, China National Knowledge Infrastructure, Wanfang Data, National Institute for Health and Care Excellence, Scottish Intercollegiate Guidelines Network, and Guidelines International Network up to June 2026. Methodological and reporting quality were assessed using AGREE II and the RIGHT checklist. Factors associated with guideline quality were examined using regression and subgroup analyses. Two AI agents were compared with human consensus with and without a structured guideline appraisal workbook, followed by external validation using 6 anterior cruciate ligament reconstruction CPGs. Results We included 227 CPGs (163 English-language, 64 Chinese-language). After introducing a structured guideline appraisal workbook, agreement among human experts improved markedly—mean intraclass correlation coefficients (ICCs) increased from –0.09 to 0.66 to 0.84-0.92 across AGREE II domains. Overall guideline quality remained low, with 35.9% (SD 18,8%) applicability and 52% (SD 17.2%) stakeholder involvement. English-language guidelines outperformed Chinese-language guidelines in scope and purpose (mean 74.64, SD 15.4 vs mean 68.88, SD 13.9; P=.004) and applicability (mean 39.14, SD 18.6 vs mean 27.54, SD 16.7; P